Operations and supply chain management the core - Jacobs, F. Robert (McGraw-Hill/Irwin series operations and decision sciences)
The third edition of Operations and Supply Chain Management: The Core focuses on the important "core" concepts in the dynamic field of operations. Just as lava flows from the core of the earth, operations and supply chain management is the core of business. Material must flow through supply chain processes to create cash output and input. This new edition has an increased focus on supply chain analytics involving the analysis of data to better solve business problems.